2016
DOI: 10.1021/acs.bioconjchem.6b00298
|View full text |Cite
|
Sign up to set email alerts
|

First Crystal Structure for a Gold Carbene–Protein Adduct

Abstract: The X-ray structure of the adduct formed in the reaction between the gold N-heterocyclic carbene compound Au(NHC)Cl (with NHC = 1-butyl-3-methyl-imidazole-2-ylidene) and the model protein thaumatin is reported here. The structure reveals binding of Au(NHC)(+) fragments to distinct protein sites. Notably, binding of the gold compound occurs at lysine side chains and at the N-terminal tail; the metal binds the protein after releasing Cl(-) ligand, but retaining NHC fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…As observed for previously reported Au(III)/protein adducts, this type of compound favors exchange of the original ligands and further possible reduction to Au(I) species. 61−63 It is worth mentioning that so far only a few X-rays structures of gold complexes (Au(I) and Au(III)) with proteins have been reported, 64 where these metal ions bind to Cys, 65,66 Lys, 67 or His residues. 68 Further studies are necessary to validate the binding mode of the cyclometalated Au(III) complexes to urease.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…As observed for previously reported Au(III)/protein adducts, this type of compound favors exchange of the original ligands and further possible reduction to Au(I) species. 61−63 It is worth mentioning that so far only a few X-rays structures of gold complexes (Au(I) and Au(III)) with proteins have been reported, 64 where these metal ions bind to Cys, 65,66 Lys, 67 or His residues. 68 Further studies are necessary to validate the binding mode of the cyclometalated Au(III) complexes to urease.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“… 72 , 73 , 85 , 86 On the other hand, the reduced uptake seen for 3 (in contrast to 1 and 5 ) is ascribed to irreversible sequestration by serum proteins, a conclusion that is consistent with recent structural work showing that mono-NHC ligated Au( i ) complexes bind lysine residues within protein models. 87 , 88 On the basis of the present work, we propose that such irreversible binding be avoided if the goal is to achieve cell uptake and targeting of the antioxidant network ( Fig. 6a and b ).…”
Section: Discussionmentioning
confidence: 94%
“…Although as a soft metal ion Au(I) shows a marked preference for soft ligands such as thiols of cysteines and thioethers of methionines [32], multiple X-ray crystallography data have shown that Au(I) ions can coordinate solvent-exposed His [33,34,35], even in the presence of free thiols. In particular, a recent X-ray study [36] has shown that in the absence of free cysteines, methionines, and histidines, these Au(I)(NHC) gold compounds are able to bind the side chains of Lys and Arg residues or the N-terminal Ala amino group.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the interaction of gold carbene compounds with many proteins (for example, TrxR, phosphatases, glutathione reductases, serum albumin, Atox-1, or thaumatin) has now been widely examined [1,7,17,19,25,28,29,30,36,37,38,39,40,41,42,43,44], their detailed mechanisms of reaction with protein side chains are still lacking. In this study, we compute the reactivity of the neutral Au(I)NHC complex (Me 2 Imy)AuCl, or IMeAuCl, with water, and with the main binding sites in a protein or a polypeptide, i.e., the side chains of arginine, aspartic acid, asparagine, cysteine, glutamic acid, glutamine, histidine, lysine, methionine, and selenocysteine residue, and the N-terminal group.…”
Section: Introductionmentioning
confidence: 99%